MUTUAL SYNTHESIS OF MEDIEVAL ISLAM GNOSEOLOGY AND THEOLOGY (Scientific journal of the Fergana State University, 2023)
This article examines the stages of formation and development of the system of Oriental, gnoseological and theological views of the Middle Ages, the results of interaction, harmonious and  controversial aspects.